"We're Going to Make Lemonade Out of Lemons": Urban Principals, Emotion, and Race to the Top Implementation. (December 2015) - Wieczorek, Douglas; Theoharis, George
This study reports on four urban middle- and high school principals' emotionally shaped sense making of Race to the Top policies and their ability to balance the competing demands of teachers' emotional needs with the charge to implement mandated, accountability-driven, instructional, and evaluation changes in their schools. Despite the pressure and apprehension about Race to the Top, they expressed optimism and worked to align their schools to the established policy frameworks while honoring teachers' feelings and supporting their needs at the same time. This study provides implications for research, practice, and leadership development regarding how social, cognitive, and emotional factors affect principals' instructional leadership, particularly how they navigate changes and increasing, multilevel, policy-driven educational pressures.